Applications of Iron Oxide-Based Magnetic Nanoparticles in the Diagnosis and Treatment of Bacterial Infections - Xu, Chen; Akakuru, Ozioma Udochukwu; Zheng, Jianjun; Wu, Aiguo (Frontiers in Bioengineering and Biotechnology, 2019)
Diseases caused by bacterial infections, especially drug-resistant bacteria have seriously threatened human health throughout the world. It has been predicted that antimicrobial resistance alone will cause 10 million deaths per year and that early diagnosis and therapy will efficiently decrease the mortality rate caused by bacterial infections. Considering this severity, it is urgent to develop effective methods for the early detection, prevention and treatment of these infections. Until now, numerous efforts based on nanoparticles have been made to detect and kill pathogenic bacteria. Iron oxide-based magnetic nanoparticles (MNPs), as potential platforms for bacteria detection and therapy, have drawn great attention owing to their magnetic property. These MNPs have also been broadly used as bioimaging contrast agents and drug delivery and magnetic hyperthermia agents to diagnose and treat bacterial infections. This review therefore overviews the recent progress on MNPs for bacterial detection and therapy, including bacterial separation and enrichment in vitro, bacterial infection imaging in vivo, and their therapeutic activities on pathogenic bacteria. Furthermore, some bacterial-specific targeting agents, used to selectively target the pathogenic bacteria, are also introduced. In addition, the challenges and future perspective of MNPs for bacterial diagnosis and therapy are given at the end of this review. It is expected that this review will provide a better understanding toward the applications of MNPs in the detection and therapy of bacterial infections.